Understanding The Factors Influencing The Interest in Adopting Battery Electric Vehicles (BEV): A Quantitative Investigation - Cakti Vyasha, Bhisma (Syntax Literate, 2025)
This research employs a quantitative design to investigate factors influencing Battery Electric Vehicle (BEV) adoption intentions among Indonesians, using the framework developed by Elena Higueras-Castillo et al. (2021). By utilizing IBM SPSS, the study examines psychological and social factors such as attitudes towards BEVs, subjective norms, perceived behavioral control, and intention to use BEVs. Multiple hypotheses are tested using multiple regression analysis. Survey responses from 145 participants are analyzed using descriptive statistics, correlation analysis, multiple regression, and factor analysis to identify patterns and relationships. The study ensures validity and reliability through pre-testing the questionnaire and adhering to ethical guidelines. Statistical analyses reveal that attitudes, subjective norms, and perceived behavioral control significantly influence residents' readiness to adopt BEVs. The findings fill a knowledge gap in BEV adoption dynamics within Indonesia, offering insights for policymakers, urban planners, and other stakeholders. Based on the results, recommendations are made for policy interventions, infrastructure investments, and public awareness campaigns to accelerate the transition towards electric mobility. These insights can be leveraged to effectively market BEVs to new potential consumers by highlighting the positive attitudes, social norms, and perceived control factors that drive adoption.